Overview Of Family Emotional And Instrumental Support Of Schhizophrenic Patients With Social Isolation - Metty Nurherliyany; Septian Try Rahmana; Rosmiati (LPPM STIKes Muhammadiyah Ciamis, 2020)
Background: Schizophrenia is a persistent psychotic disorder that includes disturbances in behavior, emotions, and perceptions. Symptoms of schizophrenia are social isolation. Social isolation is the state of an individual experiencing a decline or even being completely unable to interact with other people around him. The physical impact of patients with social isolation if not addressed will cause more serious problems including; self-care deficits, and hallucinations which can eventually lead to violent behavior and suicidal actions. Family support or the role of the family in educating family members greatly influences the occurrence or absence of mental disorders. Objective: This study aims to describe the family's emotional and instrumental support for schizophrenic patients with social isolation in the work area of the Ciamis Health Center in 2020. Method: The research method used is descriptive. The population in this study were families of schizophrenic patients with social isolation disorders in the Work Area of the Ciamis Health Center as many as 15 people. Samples were taken using the total sampling technique. Result: The results showed that most of the emotional support in schizophrenic patients with social isolation was categorized as unsupportive by as many as 9 people (60%) and instrumental support in schizophrenic patients with social isolation was mostly categorized as unsupportive by as many as 8 people (53.3%). Conclusion: description of emotional support and instrumental support in schizophrenic patients with social isolation in the Work Area of the Ciamis Health Center, most of which are categorized as not supportive.